Congenital urethroperineal fistula - Tatsuma Sakaguchi; Yoshinori Hamada; Hideyuki Matsushima; Hiroshi Hamada; Takeshi Shirai; Yusuke Shigeta; Yusuke Nakamura; Takashi Doi; Masanori Kon (Elsevier, 2018)
Background: Congenital urethroperineal fistula is an extremely rare anomaly in which a second channel rises from the prostatic urethra and opens onto the perineum. This entity resembles the hypospadiac type of urethral duplication, but resection of the ventral channel is simple and curative. Case: A 4-year-old healthy boy had a small pimple on his perineum that yielded a small amount of whity discharge. Discharge occurred every one month for three years. The patient had no history of incontinence or urinary tract infection. Physical examination revealed a small opening to the median perineal raphe below the scrotum. Voiding cystourethrogram showed a normal urethra but no fistula was demonstrated. Fistulography failed due to closure of external orifice at the small pimple. MRI revealed abnormal sagittal tract from the pimple to the prostatic urethra. A circular incision was made around the pimple and the dissection was performed along the fistula. The fistula was ligated. Histopathologic examination of the fistula revealed that it was lined with squamous epithelium. Two months after surgery, incision of the abscess was performed. He has been well with 8 months postoperatively. Conclusion: Simple resection of the ventral channel of the urethroperineal fistula is curative. While both are rare entities, differentiation to the hypospadiac type of urethral duplication is crucial for definite treatment.